DEVELOPMENT OF CHEMISTRY LEARNING OUTCOME ASSESSMENT INSTRUMENTS (MULTIPLE CHOICE) ON HYDROCARBON MATERIAL - Manullang, Enjelika; Daulay, Rabiah Afifah; Nadira, Fathin; Sihaloho, Kayra Aprilia Yosephin; Azhara, Nazwa; Nazihah, Nazwa (LAVOISIER: Chemistry Education Journal, 2025)
This study aims to develop an assessment instrument in the form of a multiple-choice objective test on hydrocarbon material in senior high school chemistry. The research method used is research and development (RD), involving steps such as material analysis, test item construction, validation, field trials, and item analysis. The developed instrument consists of 30 items based on the learning outcomes in the "Kurikulum Merdeka". Validity testing using Pearson correlation shows that 29 out of 30 items are valid (r ≥ 0.388; sig. 0.05). Reliability testing using Cronbach's Alpha resulted in a score of 0.965, indicating very high reliability. These findings suggest that the developed test instrument is valid and reliable for evaluating students' understanding of hydrocarbon concepts.